La Audiodescripción desde la representación del conocimiento general. Configuración semántica de una gramática local del texto audiodescrito - Jiménez Hurtado, Catalina (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Audio Description is a new text type which offers the prototypical receiver – blind or partially sighted people – a narrated representation of what is occurring at specific moments in the other audiovisual text to which it is subordinated. An AD script is subject to multiple subordination: to what is happening on the screen, to the distribution of silent spaces in the other text, and to the amount of time provided in each space. This fact, however, does not prevent the AD script from offering a representation of the general knowledge encoded by specific fragments of the film. Such a representation of knowledge, understood as the description in words or other signs of a specific reality, may serve as a semantic basis for the creation of a local grammar of AD scripts.